Being human the problem of agency - Archer, Margaret Scotford (Cambridge University Press, 2000)
Humanity and the very notion of the human subject are under threat from postmodernist thinking which has declared not only the 'Death of God' but also the 'Death of Man'. This book is a revindication of the concept of humanity, rejecting contemporary social theory that seeks to diminish human properties and powers. Archer argues that being human depends on an interaction with the real world in which practice takes primacy over language in the emergence of human self-consciousness, thought, emotionality and personal identity - all of which are prior to, and more basic than, our acquisition of a social identity. This original and provocative new book from leading social theorist Margaret S. Archer builds on the themes explored in her previous books Culture and Agency (CUP 1988) and Realist Social Theory (CUP 1995). It will be required reading for academics and students of social theory, cultural theory, political theory, philosophy and theology